Assessment of the relationship between non‐alcoholic fatty liver disease and diabetic complications. Issue 6 (20th April 2016) - Yan, Li‐hui; Mu, Biao; Guan, Yue; Liu, Xinyu; Zhao, Nan; Pan, Da; Wang, Shao‐zhen
Abstract: Aims/Introduction: Non‐alcoholic fatty liver disease (NAFLD) is a metabolic disorder of the liver. The relationship between NAFLD and type 2 diabetes remains largely unknown. The aim of the present study was to determine the incidence of complications arising from the interaction between NAFLD and type 2 diabetes. Materials and Methods: A total of 212 individuals with type 2 diabetes were included in the study. The presence of NAFLD was determined in individuals using abdominal ultrasonography for the diagnosis of fatty liver disease. Patients were divided into three groups based on the duration of diabetes and NAFLD diagnosis. Type 2 diabetes patients were placed in group A; patients with type 2 diabetes longer than NAFLD were placed in group B; and patients with NAFLD longer than type 2 diabetes were placed in group C. All individuals had undergone electrocardiogram, blood pressure measurements, and thorough medical history and physical examinations (Doppler ultrasound, electrophysiology, fundoscopy, cardiac computed tomography). Laboratory measurements included fasting blood glucose, glycated hemoglobin, oral glucose tolerance test, liver and renal function, lipid profile, and urinary albumin excretion. Results: Compared with groups A and B, the patients of group C showed a higher prevalence of significant coronary artery disease and hypertension ( P < 0.05). Compared with groups A and B, the patients of group C showed a lower prevalence of diabetic retinopathy and diabetic peripheral neuropathy ( P < 0.05). There was no significant difference in the prevalence of diabetic nephropathy among the three groups ( P > 0.05). Conclusions: NAFLD combined with type 2 diabetes is associated with the presence of significant coronary artery disease and hypertension. Abstract : As NAFLD were strictly related to T2DM, an understanding of NAFLD and diabetic complications is imperative. Previous studies did not distinguish the temporal sequence of NAFLD and T2DM. We found that different temporal sequence of NAFLD and T2DM have different complications.